A Systematic Literature Review on Technology-Based Learning Media in ECE to Face Society 5.0 Era - Lisa Nur Maulidia; Suparno Suparno; Umniyah Juman Rosyidah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Education is a bridge between society's mastery of technology and the demands of life that are increasingly familiar with the technology. Consequently, it is essential to comprehend the readiness of the education sector, particularly the employed learning media. This study investigates the readiness of technology-based learning media in the field of early childhood education for the era of society 5.0. This study is included in systematic literature review which aims to examine articles with similar topics for review and analysis. Document identification is done by reviewing the title, abstract, and keyword of the article. Temporary, the content analysis study examines the forms and methods, components, and the advantages of media consumption. The results of study resulted in two key findings, namely a summary of the characteristics of the types of technology-based learning media that must be owned so that they are relevant to be applied in the era of society 5.0. Types of learning media that have been successfully synthesized include games, digital storytelling, LMS, augmented reality, and interactive multimedia. While the characteristics that learning media must have to be relevant to Society 5.0 include adaptive, innovative, personalized, flexible, and integrated with various innovative devices such as IoT, AI, and big data. Practical recommendations that can be used are efforts to continue upgrading skills, especially those related to technology and prioritizing elements of children's fun, attractiveness, and increasing opportunities for children to interact with technology in learning activities.